2019
DOI: 10.1080/19768354.2018.1557743
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxic preconditioning on memory evaluated using the T-maze behavior test

Abstract: Perioperative brain ischemia and stroke are leading causes of morbidity and mortality. Brief hypoxic preconditioning is known to have protective effects against hypoxic-ischemic insult in the brain. Current studies on the neuroprotective effects of ischemic preconditioning are based on histologic findings and biomarker changes. However, studies regarding effects on memory are rare. To precondition zebrafish to hypoxia, they were exposed to a dissolved oxygen (DO) concentration of 1.0 ± 0.5 mg/L in water for 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 25 publications
7
12
0
Order By: Relevance
“…Similar to our previous findings, a four-day training period was sufficient to allow zebrafish to develop a preference for a particular target compartment, even in the absence of colored cellophane and food during the testing period. Approximately 10 min of hypoxia reversed the effects of training and induced cerebral injury, consistent with our previous results [21,26].…”
Section: Table 1 T-maze Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Similar to our previous findings, a four-day training period was sufficient to allow zebrafish to develop a preference for a particular target compartment, even in the absence of colored cellophane and food during the testing period. Approximately 10 min of hypoxia reversed the effects of training and induced cerebral injury, consistent with our previous results [21,26].…”
Section: Table 1 T-maze Resultssupporting
confidence: 92%
“…Notably, zebrafish have specific color preferences [32]. We previously employed a similar zebrafish behavior model using color preferences in the absence of food rewards [21,26]. Similar to our previous findings, a four-day training period was sufficient to allow zebrafish to develop a preference for a particular target compartment, even in the absence of colored cellophane and food during the testing period.…”
Section: Table 1 T-maze Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Notably, zebra sh have speci c color preferences [32]. We previously employed a similar zebra sh behavior model using color preferences in the absence of food rewards [21,26]. Similar to our previous ndings, a four-day training period was su cient to allow zebra sh to develop a preference for a particular target compartment, even in the absence of colored cellophane and food during the testing period.…”
Section: Discussionmentioning
confidence: 67%
“…Power analysis revealed that a minimum sample size of 10 for each group would be required to achieve a power of 80% at a signi cance level of 5%. Power analysis was calculated from results of our prior experiment [26]. To allow for exclusions, total sample size was prospectively set at 48 zebra sh (12 for each group).…”
Section: Sample Size Calculationmentioning
confidence: 99%